Coenzyme Q10 supplementation in non-alcoholic fatty liver disease: an overview. (2nd March 2020) - Mantle, David; Hargreaves, Iain P
Abstract : Non-alcoholic fatty liver disease (NAFLD) is the most common liver disorder in the UK, for which little effective conventional treatment is available. Mitochondrial dysfunction, oxidative stress and inflammation have been implicated in the pathogenesis of NAFLD. This article focuses on the role of the vitamin-like substance coenzyme Q10 (CoQ10) in NAFLD, since CoQ10 plays a key role in mitochondrial function, as well as having antioxidant and anti-inflammatory action. CoQ10 levels are depleted in NAFLD, and studies in animal models and human subjects have indicated that supplementation with CoQ10 can significantly reduce oxidative stress and the inflammation characteristic of NAFLD. In addition, NAFLD patients are at increased risk of developing heart failure, and supplementary CoQ10 may help to reduce this risk. Supplementary CoQ10 is generally well tolerated, with no significant adverse effects reported in long-term use.